Biomechanical simulations of crystalline lens oscillations resulting from the changes in the gaze in an accommodated eye - Dahaghin, Ali; Salimibani, Milad; Boszczyk, Agnieszka; Jóźwik, Agnieszka; Grasa, Jorge; Przeździecka-Dołyk, Joanna; Siedlecki, Damian (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeThe goal of the study is to introduce a generic, versatile biomechanical model that aims to reproduce the dynamic wobbling phenomenon.MethodsA systematic strategy is used, which includes a) capturing the in vivo data on a group of healthy volunteers, b) analyzing the changes in Purkinje images over time, and c) performing the combined biomechanical and optical simulations to develop the model that might be useful for understanding the mechanical behavior of the lens during wobbling and its influence on ocular dynamics.ResultsExamples of lens wobbling patterns for six measured eyes were presented, and parameters characterizing the oscillatory motion were determined, including frequency of oscillations, Q-factor, damping factor and time constant. The average values of these parameters are the following: frequency: 20.0 ± 2.4 Hz; Q-factor: 1.86 ± 0.44; damping factor: 0.27 ± 0.06; time constant: 0.11 ± 0.06 s. The data reproduced by means of simulations: frequency: 19.3 Hz; Q-factor: 2.17; damping factor: 0.23; time constant: 0.15 s. This comparison reveals a good agreement between the measured and reconstructed data with the values being within the standard deviation limits.ConclusionThe developed generic model together with the presented methodology is able to reconstruct the typical crystalline lens wobbling dynamics with a satisfying accuracy. However, the observed intersubject variability highlights the need for personalized biomechanical models. The introduced model may constitute the basis for future individualization of the data, bringing broad perspectives for prospective investigations aimed to explain the biomechanical mechanisms within the eye.